Litteratur. - Andenæs, Johs.; Haslund, A.; Christiansen, Karl O.; Johnsen, Jon; Smith, Jørgen; Hurwitz, Stephan; Waaben, Knud; Marcus, Franz; Aude-Hansen, Carl; Christie, Nils (Nordisk Tidsskrift for Kriminalvidenskab, 1955)
Intet resumé